IDENTIFIKASI AKUIFER AIR TANAH DI KEC. TAMANSARI, KOTA TASIKMALAYA DENGAN METODE GEOLISTRIK - Wibowo, Mardi (Jurnal Hidrosfir Indonesia, 2009)
Along with increase in population and economic growth inTasikmalaya Residence cause the need of water is increased too.The majority these need take from groundwater resources.Occurrence groundwater resources depends on many factor likelandform (landscapes), geology, precipitation, land use, etc.Resistivity geoelectric survey (method) can detect groundwaterresources occurrence. The goals of this survey is to predict geometryand distribution of groundwater reservoir (aquifer). This survey useresisitivity method with Schumblerger Configuration. Generally,underground condition of Tamansari area consist of 4 layers oflithology i.e. pebbly sandstone, sandstone, clayey sandstone andsandy claystone. Sandstones have good potential as aquifer.Sandstone layer is evenly distributed in Tamansari area at depthbetween 1 m – 10 m. For shallow groundwater resources exploitationshould be directed at south east and south west part of Tamansariarea; while for deep groundwater resources exploitation can directedanywhere at depth more than 100 m.